Effect of environmental CSR initiatives on potential stakeholders’ perception of non-environmentally friendly sporting events - Yong-chae Rhee; Yukyoum Kim (Journal of Applied Sports Management, 2021)
The protection of the natural environment is increasingly being perceived as a pillar of CSR. Although most professional sport organizations in the United States participate in some form of philanthropic activity, little research has examined how non-environmentally friendly sport organizations can effectively communicate their environmental initiatives. Two different CSR approaches (Environmental and Nationalistic) by NASCAR were exposed to potential stakeholders to examine the changes in the perception (Attitude, Reputation, Identification, and Perceived CSR) of the organization. We analyzed the MIMIC model to compare the means on the latent constructs. Environmental approach showed positive changes in potential stakeholders’ perception toward NASCAR. Whereas, the Nationalistic CSR approach had no significant impact on potential stakeholders’ perception of the organization. The findings suggest CSR can be an opportunity for organizations like NASCAR to have a positive non-product message for potential stakeholders depending on how they communicate these programs.
Keywords: Consumer Behavior; CRM; Environmental Marketing; NASCAR; Nationalistic Marketing